RASIO KEUANGAN DAN HARGA SAHAM SYARIAH PADA JAKARTA ISLAMIC INDEX - Wildan Army Abdillah; Syarif Alamsyah; Rengga Madya Pranata (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2021)
The purpose of this study is to analyze the effect of Current ratio, Return on Assets, and Debt to equity ratio on Islamic stock prices in companies listed on the Jakarta Islamic Index 2015-2020, either partially or simultaneously. The type of research used is verification with the Explanatory Survey method. The type of data used is quantitative data with a sampling method, namely Purposive Sampling. The data analysis method used is Panel Data Regression Analysis, t-test, F-test, and Coefficient of Determination Test. The results showed that partially Current ratio and Debt to Equity ratio had no significant effect on Islamic stock prices. Meanwhile, return on assets has a positive and significant effect on stock prices. Then, simultaneously Current ratio, Return on Assets, and Debt to equity ratio affect stock prices. The Adjusted-Square value in the study is 0.123729, this means that the variables Current ratio, Return on Assets, and Debt to equity ratio only contribute 12.37% influence on stock prices and the remaining 87.63% is influenced by other variables. outside the research model